A genome-wide association study to identify candidate genes for erectile dysfunction. Issue 4 (15th December 2020) - Kazemi, Elham; Zargooshi, Javaad; Kaboudi, Marzieh; Heidari, Parviz; Kahrizi, Danial; Mahaki, Behzad; Mohammadian, Youkhabeh; Khazaei, Habibolah; Ahmed, Kawsar
Abstract: Erectile dysfunction (ED) can be caused by different diseases and controlled by several genetic networks. In this study, to identify the genes related to ED, the expression profiles of normal and ED samples were investigated by the Gene Expression Omnibus (GEO) database. Seventeen genes were identified as associated genes with ED. The protein and nucleic acid sequences of selected genes were retrieved from the UCSC database. Selected genes were diverse according to their physicochemical properties and functions. Category function revealed that selected genes are involved in pathways related to humans some diseases. Furthermore, based on protein interactions, genes associated with the insulin pathway had the greatest interaction with the studied genes. To identify the common cis -regulatory elements, the promoter site of the selected genes was retrieved from the UCSC database. The Gapped Local Alignment of Motifs tool was used for finding common conserved motifs into the promoter site of selected genes. Besides, INSR protein as an insulin receptor precursor showed a high potential site for posttranslation modifications, including phosphorylation and N-glycosylation. Also, in this study, two Guanine-Cytosine (GC)-rich regions were identified as conserved motifs in the upstream of studied genes which can be involved in regulating the expression of genes associated with ED. Also, the conserved binding site of miR-29-3p that is involved in various cancers was observed in the 3′ untranslated region of genes associated with ED. Our study introduced new genes associated with ED, which can be good candidates for further analyzing related to human ED.